2016
DOI: 10.4314/star.v4i2.14
|View full text |Cite
|
Sign up to set email alerts
|

Livestock Grazing in Afromontane Grasslands in the Northern Bale Mountains, Ethiopia: Implications for Bird Conservation

Abstract: The aim of this study was to examine the effects of livestock grazing on Afromontane grassland bird assemblages in the Bale Mountains, Ethiopia. Birds were counted along 28 (14 in ungrazed site and 14 in grazed site) 1 2014) and dry season (November 2014). In addition, height and cover of shrubs, grasses and herbs were recorded within 10m ×10m quadrats established along each transect at a distance of 250m. These data were used to abundances of overall assemblages and guilds (habitat, feeding and/or conservatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
(33 reference statements)
1
6
0
Order By: Relevance
“…It is well known that Lantana camara performs well in human disturbed canopy gaps across the tropics (Totland et al 2005) and negatively impacts the establishment of native plants through shading, jeopardizing regeneration of the native flora (Sharma & Raghubanshi 2007). Also studies conducted elsewhere have found that species richness and diversity can increase with human disturbances due to influx of shrubs following disturbance (Sahu et al 2008;Asefa et al 2015). In the long term, increasing cover of such disturbance affiliated species may jeopardize recovery and establishment of native species (Asefa et al 2015).…”
Section: Community Composition and Human Disturbancementioning
confidence: 99%
“…It is well known that Lantana camara performs well in human disturbed canopy gaps across the tropics (Totland et al 2005) and negatively impacts the establishment of native plants through shading, jeopardizing regeneration of the native flora (Sharma & Raghubanshi 2007). Also studies conducted elsewhere have found that species richness and diversity can increase with human disturbances due to influx of shrubs following disturbance (Sahu et al 2008;Asefa et al 2015). In the long term, increasing cover of such disturbance affiliated species may jeopardize recovery and establishment of native species (Asefa et al 2015).…”
Section: Community Composition and Human Disturbancementioning
confidence: 99%
“…Moreover, identifying the existing threats in a particular area is also essential for developing effective conservation efforts and management actions. 8,11 Although, birds are among the key components of the earth's biodiversity, information on birds check list is still far from complete for most species in many countries including Ethiopia, and this might be an obstacle in the development effective conservation planning at the local/regional, national and global scales. 6,7,12 In Ethiopia, some studies are conducted on the diversity, distribution and abundance of birds predominantly in protected areas such as National parks.…”
Section: Introductionmentioning
confidence: 99%
“…Habitat disturbance has also a negative impact for forest specialist species as they do not have any alternative foraging or breeding sites (Asefa et al ., 2017). According to Asefa et al ., (2015) allowing large and repetitive livestock population in to unprotected area will also lead to los of grassland specialist species.…”
Section: Discussionmentioning
confidence: 99%